Consumer Confusion Shopping in E-Commerce - Athallah Safir Manaf; Prasetyo Hadi (Eduvest - Journal of Universal Studies, 2025)
The growth of the digital trading industry in Indonesia is rapid and strategically significant for the economy. However, this growth also presents challenges, specifically consumer confusion when shopping online. This study aims to identify factors causing consumer confusion, determine the most dominant factor, and formulate strategies to mitigate this confusion. The main factors identified are excessive product choices, product similarities, and ambiguous or overwhelming information. Such confusion negatively affects consumer trust and satisfaction, influencing their purchasing decisions. Strategies proposed to reduce confusion include clarifying product information, simplifying choices, and enhancing communication between sellers and buyers. These findings offer practical benefits for digital businesses aiming to improve service quality and consumer shopping experiences.